2019
DOI: 10.1108/ijchm-11-2017-0761
|View full text |Cite
|
Sign up to set email alerts
|

Emotions as core building blocks of an experience

Abstract: PurposeTo stimulate the discussion in the fields of hospitality, tourism, and leisure on what exactly constitutes "an experience" and how to measure it, we unpack the experience construct into its core constituent elements, namely, emotions. ApproachThe paper reviews insights from psychology and cognitive neuroscience that define experiences as a fine-grained temporal succession of emotions that occur during an experiential episode. Limitations of current methods for measuring experiences are discussed, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 82 publications
8
121
1
5
Order By: Relevance
“…This research found that intense emptions is a consequent condition of novelty in recalled events. Previous studies recognize that emotions related to the memorability of the tourism experiences (Bastiaansen et al, 2019). Findings of the present research indicate that novelty may lead to positive as well as negative emotions in the tourism experiences (Kim J. H et al, 2012;Lin et al, 2014;Wang et al, 2017).…”
Section: Consequences Of Novelty In the Tourism Experiencessupporting
confidence: 45%
See 2 more Smart Citations
“…This research found that intense emptions is a consequent condition of novelty in recalled events. Previous studies recognize that emotions related to the memorability of the tourism experiences (Bastiaansen et al, 2019). Findings of the present research indicate that novelty may lead to positive as well as negative emotions in the tourism experiences (Kim J. H et al, 2012;Lin et al, 2014;Wang et al, 2017).…”
Section: Consequences Of Novelty In the Tourism Experiencessupporting
confidence: 45%
“…Novelty in a pleasurable tourism experience is associated with suddenness or unexpectedness and with emotions such delight, surprise, and enjoyment (Ortony et al, 1988;Scherer, 1993;Roseman et al, 1996). Emotions are considered as critical for the delivery of MTEs (Bastiaansen et al, 2019;Skavronskaya et al, 2019b). Strong emotions resulting from a novel experience result in vivid memories, created through the secretion of chemicals including dopamine (Moyle et al, 2019).…”
Section: Novelty Experience Emotion and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been broadly recognized that emotions embody the value in tourism experiences (Knobloch, Robertson, & Aitken, 2017), are important mediators of recommendation and other target outcomes (Hosany & Gilbert, 2010;Prayag, Hosany, & Odeh, 2013), and fuel the social meanings of tourism experiences (Mitas, Yarnal, & Chick, 2012). Emotions also give practitioners the best entry point for measuring and managing experiences (Bastiaansen et al, 2019;Li, Scott, & Walters, 2015;Moyle, Moyle, Bec, & Scott, 2017;Skavronskaya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it is not clear if simply more emotion during a tourism experience is better. Furthermore, cross-sectional studies leave the role of temporal dynamics unexplained (Bastiaansen et al, 2019). In the present paper, we report on an experience measurement of a complex tourism experience, comprised of a museum visit and village tour, to address the relationship between temporal and spatial dynamics of experience and overall experience evaluation.…”
Section: Introductionmentioning
confidence: 99%